Exploring the mechanisms for records management's digital transformation: a case study from China. (4th December 2020) - Yang, Qianqian; Du, Yuqiao; Shi, Linyu
Abstract : Purpose: The purpose of this study is to explore the mechanisms underlying the transformation of records management (RM) to digital processes in the context of electronic records management systems (ERMS). The aim is to facilitate the evaluation of the long-term performance of ERMS and the effectiveness of the current standards. Design/methodology/approach: Qualitative methods, such as participant observation and the constructivist grounded theory, were applied on a case of ERMS implementation in the Chinese public sector. Findings: The results revealed that the application of transition-oriented ERMS would stimulate restructuring in the RM pattern and expectation on the functions of ERMS, with information quality underlying as a key challenging factor. The above-stated factors together drive the digital transformation of RM. A model for this mechanism is provided in the present study. Research limitations/implications: The selected case serves as an example for the cases that are not conditional on enforcing the electronic documents and RMS. As preliminary research, only one case has been studied here. However, it is possible to conduct other case studies to develop a further understanding of the transformation process. Originality/value: The novelty of the present study is that it draws attention to the challenges encountered in moving RM towards digital transformation, by providing a theoretical foundation for developing sustainable evaluations of the ERMS and the associated current standards.